Tree diversity, forest structure and species composition in a logged-over mixed dipterocarp forest, Bintulu, Sarawak, Malaysia - Malcom, Demies; Hiromitsu, Samejima; Alexander Kiew, Sayok; Gabriel Tonga, Noweg (2019)
The Anap Muput Forest Management Unit (AMFMU) located in Bintulu, Sarawak, Malaysia is a production forest. It have undergone at least one or two cycle of selective logging where valuable timber species are depleting. Therefore the structure, composition and productivity of the re growth forests are quite different from the virgin stands. Measuring the diversity is one of the ways to access the soundness of ecological ecosystems. This study aim to collect information on tree diversity, forest structure and species composition. A total of 61 circular plots of 25-m radius were established covering a total area of 7.67 hectares. Trees with diameter at breast height (DBH) of 10 cm and above were recorded. Species composition, diversity, relative density (RD), relative basal area (RBA) and relative frequency (RF) and important value index (IVI) were calculated. A total of 5,871 trees comprised of 66 families, 208 genera and 827 species were recorded. Dipterocarpaceae was the most dominant family with 31.8% of trees. Shorea was the dominant genus, while Macaranga hosei of Euphorbiaceae with 193 trees is the most dominant species here. Shorea collaris was the highest record for Dipterocarpaceae with 176 stands. The highest IVI of trees in lowland dipterocarp forest was Shorea macroptera ssp. baillonii with the value of 84.73 though it only represented 1.8% of the total IVI of the area. At Shannon-Weiner diversity index (H’) of 3.44, the diversity of logged-over lowland dipterocarp forest in the study area is considered highly diverse. The results of this study strengthen the importance to manage the forest sustainably as timber industry is important for the state’s economy. KEYWORDS: Biodiversity; Tree species; Diversity; Sample plots; Mixed Dipterocarp Forest